Sudden death in a patient with long QT syndrome presenting with an epileptic phenotype. Issue 6 (21st March 2020) - Sharma, Esseim; Gannon, Stephen; McCauley, Brian; Chu, Antony F.
Abstract: Patients with epilepsy suffer from a higher mortality rate than the general population, a portion of which is not due to epilepsy itself or comorbid conditions. Sudden unexpected death in epilepsy (SUDEP) is a common but poorly understood cause of death in patients with intractable epilepsy and often afflicts younger patients. The pathophysiology of SUDEP is poorly defined but does not appear to be related to prolonged seizure activity or resultant injury. Interestingly, a subset of patients with confirmed long QT syndrome (LQTS) present with a seizure phenotype and may have concurrent epilepsy. In this case, we present a patient who initially presented with a seizure phenotype. Further workup captured PMVT on an outpatient event monitor, and the patient was subsequently diagnosed with LQTS1. A substantial number of patients with LQTS initially present with a seizure phenotype. These patients may represent a subset of SUDEP cases resulting from ventricular arrhythmias. Appropriate suspicion for ventricular arrhythmias is necessary for proper arrhythmia evaluation and management in patients presenting with epilepsy.